História de uma História - Bandecchi, Brasil (Anais do Museu Paulista: História e Cultura Material, 1981)
Júlio Frank, born in Gotha in 1808, Germany, isa very questioned personality in the History of Brazil, mainly São Paulo. He was professor of a course attached to the Faculty of Law in this city. He founded in 1831 a secret society named “Burschenschaft” known as the “Bucha” with a philanthropical purpose and liberal approach. Júlio Frank wrote the first Universal History published in Brazil. He and Libero Badaró introduced the liberalism in São Paulo. Such a personality suffered, of course, many criticisms but has also a great number of defenders. Brasil Bandecchi in his paper “Bucha, the Freemasonry and the liberal spirit” herein presented, exposes the history of Júlio Frank’s “Summary of the Universal History”, issued in 1839 pointing out the issued unjust critics about this book. In short, Brasil Bandecchi sets forth the author and his work in his historical time so the reader will be able to grasp the real position of the book in the contexture of the didactic textbooks in Brazil.